High-temperature-resistant tough cable material and preparation method thereof

By using materials such as vinyl chloride-acrylate copolymers and advanced processes, high-temperature toughness cable materials are prepared, which solves the problem of thermal degradation and brittleness of traditional PVC cable materials at high temperatures, improves heat resistance and toughness, and extends the Cable life and improve environmental protection and processing performance.

CN119286164AInactive Publication Date: 2025-01-10LIANYING TECH (ANFU) CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411531203.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-10
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional PVC cable materials are prone to thermal degradation and brittleness in high temperature environments, resulting in degradation of cable performance. The existing modification methods are not effective, making it difficult to improve high temperature resistance and toughness at the same time.

Method used

Using vinyl chloride-acrylate copolymer, polyether ether ketone, graphene, nanotitanium dioxide, metal organic frame materials, nano alumina, antioxidants and plasticizers, through ultrasonic dispersion, surface modification, melt blending and Ultraviolet curing and other processes are used to prepare high-temperature toughness cable materials.

Benefits of technology

It significantly improves the heat resistance and toughness of the cable at high temperatures, extends the service life, enhances the flame retardant and anti-aging performance, reduces production difficulty and energy consumption, and meets environmental protection requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119286164A_ABST
    Figure CN119286164A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of cable materials, in particular to a high-temperature-resistant tough cable material and a preparation method thereof. A high-temperature-resistant tough cable material is prepared from the following components: a vinyl chloride-acrylate copolymer, polyether-ether-ketone, ethylene propylene diene monomer, graphene, nano titanium dioxide, a metal organic framework material, nano aluminum oxide, an antioxidant, a light stabilizer and a plasticizer, and a preparation method of the cable material comprises the steps of raw material pretreatment, raw material mixing, melt blending, cooling, pelletizing and the like. According to the high-temperature-resistant tough cable material and the preparation method thereof, the heat resistance and toughness of the cable material in a high-temperature environment can be remarkably improved, the problem that a traditional PVC cable material is prone to thermal degradation and embrittlement in the high-temperature environment is solved, and therefore the service life of a cable is greatly prolonged, and the reliability of the cable is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cable materials, and in particular to a high-temperature resistant and tough cable material and a preparation method thereof. Background Art

[0002] With the rapid development of the wire and cable industry, the market's performance requirements for cable materials are constantly increasing. Traditional polyvinyl chloride (PVC) cable materials are widely used in the industry due to their low cost and easy processing. However, PVC cable materials have two main problems: one is poor high temperature resistance and the other is insufficient toughness, which limits their application in high temperature environments.

[0003] The PVC cable materials currently on the market are prone to thermal degradation in high temperature environments, resulting in reduced cable performance or even failure. In addition, traditional PVC cable materials tend to become brittle under high temperature conditions, thus affecting the service life and reliability of the cable. Although a variety of modification methods have been tried to solve these problems, the results are not ideal, especially the performance in high temperature environments is still poor.

[0004] For example, Chinese patent CN110218402B discloses a high temperature flame retardant PVC cable material and its preparation method, which improves the high temperature resistance of the cable material by adding a variety of additives (triethyl citrate, silicon-containing diphenylamine, chloroprene rubber, etc.). However, these additives are easy to migrate at high temperatures, resulting in a decrease in the toughness of the cable material, thereby affecting the overall performance of the cable.

[0005] Therefore, the development of a new material that can improve the high temperature resistance of cable materials while ensuring their toughness has become an urgent need in the industry. In particular, for the heat resistance and toughness of cable materials in high temperature environments, a high temperature resistant and tough cable material and its preparation method are needed to improve the service life and reliability of the cable. Summary of the invention

[0006] In view of the deficiencies in the prior art, the present invention aims to provide a high temperature resistant tough cable material and a preparation method thereof.

[0007] A high temperature resistant and tough cable material is made of the following components in parts by weight:

[0008] 40-50 parts of vinyl chloride-acrylate copolymer, 10-20 parts of polyetheretherketone (PEEK), 8-12 parts of ethylene propylene diene monomer (EPDM), 0.5-2 parts of graphene, 2-4 parts of nano titanium dioxide (TiO2), 1-3 parts of metal organic framework materials (MOFs), 2-4 parts of nano alumina (Al2O3), 1-2 parts of antioxidant, 1-2 parts of light stabilizer and 2-4 parts of plasticizer.

[0009] Furthermore, the viscosity average molecular weight of the vinyl chloride-acrylate copolymer is 20000-50000Da.

[0010] Furthermore, the viscosity average molecular weight of the polyetheretherketone (PEEK) is 20000-40000Da.

[0011] Furthermore, the antioxidant includes antioxidant 1010 and / or antioxidant 168, the light stabilizer is a hindered amine light stabilizer, and the plasticizer includes dioctyl phthalate (DOP) and / or epoxidized soybean oil (ESO).

[0012] A method for preparing a high temperature resistant and tough cable material comprises the following steps:

[0013] (1) Raw material pretreatment: weigh each component raw material according to the weight ratio, and vacuum dry it at 100-120° C. for 2-4 hours; add graphene to an isopropanol solvent with a concentration of 15 times the weight of graphene, and disperse it evenly using an ultrasonic disperser to form a graphene dispersion;

[0014] The metal organic framework material and nano-alumina are respectively added with a surface modifier of 3% of their own weight for surface treatment, and stirred at 25°C for 30 minutes; the EPDM rubber is pre-crushed into fine particles;

[0015] (2) Mixing the raw materials: stir half of the vinyl chloride-acrylate copolymer and EPDM rubber in a high-speed mixer for 5-10 minutes to mix them evenly; stir the remaining vinyl chloride-acrylate copolymer, polyetheretherketone, nano-titanium dioxide, metal organic framework material, nano-aluminum oxide and other additives (antioxidant, light stabilizer, plasticizer) in a high-speed mixer for another 5-10 minutes to mix them evenly;

[0016] While continuing to stir in the high-speed mixer, add the graphene dispersion through the side feed port to ensure that it is evenly dispersed;

[0017] (3) Melt blending: The uniformly mixed materials are fed into a twin-screw extruder, the feed zone temperature is 180-220°C, the melting zone temperature is 320-350°C, the mixing zone temperature is 300°C, and melt blending is performed, and the screw speed is adjusted to 25-35 r / min;

[0018] The melt-blended material is extruded through a die head of an extruder, rapidly cooled, pelletized, and dried to obtain high-temperature resistant and tough cable material pellets.

[0019] Furthermore, while adding the graphene dispersion, 0.5 parts by weight of a grinding aid zinc stearate was added.

[0020] Furthermore, the rapid cooling includes air cooling or cold water bath cooling.

[0021] Furthermore, the method further comprises the following steps: (4) UV curing: spraying a solution containing a photoinitiator on the surface of the extruded material; irradiating the material with UV light to initiate a cross-linking reaction between polymer chains, and the curing time is 5-10 minutes.

[0022] Furthermore, the method further comprises the following steps: (5) microwave post-treatment: placing the UV-cured material in a microwave device and subjecting it to microwave treatment to promote the cross-linking reaction inside the material; the microwave treatment time is 5-10 minutes and the power is 300-500W.

[0023] Furthermore, in the process of surface modification of metal organic framework materials (MOFs) and nano-alumina (Al2O3), a silane coupling agent is used to modify the surface of MOFs to improve its dispersibility and compatibility in the polymer matrix; a titanate coupling agent is used to modify the surface of alumina to improve its dispersibility and compatibility in the polymer matrix.

[0024] The beneficial effects achieved by the present invention are as follows: 1. The present invention can significantly improve the heat resistance and toughness of the cable material in a high temperature environment by providing a high temperature resistant and tough cable material and a preparation method thereof, thereby solving the problem that the traditional PVC cable material is prone to thermal degradation and brittleness in a high temperature environment, thereby greatly extending the service life of the cable and improving its reliability.

[0025] 2. The present invention adopts a reasonable formula design to make the cable material have excellent flame retardant properties, which can effectively delay the spread of fire in emergency situations such as fire and improve the safety of the cable.

[0026] 3. The present invention can improve the anti-aging performance of the material by adding antioxidants and light stabilizers, so that the material can still maintain its original physical and mechanical properties after long-term exposure to outdoor environments.

[0027] 4. Compared with traditional PVC cable materials, the cable material of the present invention uses more environmentally friendly materials, reduces the emission of harmful substances, complies with the requirements of current environmental protection laws and regulations, and is conducive to sustainable development.

[0028] 5. The cable material of the present invention has excellent processing performance during the processing, making the production process smoother and reducing production difficulty and energy consumption. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The present invention is a schematic diagram of the preparation process of the high temperature resistant tough cable material. DETAILED DESCRIPTION

[0030] The technical solution of the present invention is further described below in conjunction with specific implementation methods.

[0031] Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments, unless otherwise specified, are conventional methods in the art.

[0033] Embodiment 1: A high temperature resistant and tough cable material, made of the following components in parts by weight:

[0034] 45 parts of vinyl chloride-acrylate copolymer (viscosity average molecular weight 45,000 Da), 15 parts of polyetheretherketone (PEEK) (viscosity average molecular weight 30,000 Da), 10 parts of ethylene propylene diene rubber (EPDM), 1 part of graphene, 3 parts of nano-titanium dioxide (TiO2), 2 parts of metal organic framework material (ZIF-8), 3 parts of nano-alumina (Al2O3), 2 parts of antioxidant (1 part each of antioxidant 1010 and antioxidant 168), 1 part of light stabilizer (Chimassorb944), 3 parts of plasticizer (dioctyl phthalate DOP), and 0.5 parts of grinding aid zinc stearate.

[0035] A method for preparing a high temperature resistant and tough cable material, such as Figure 1 As shown, the following steps are included:

[0036] (1) Raw material pretreatment: weigh each component raw material according to weight, and vacuum dry it at 110° C. for 3 h; add graphene to 15 parts by weight of isopropanol solvent, and disperse it evenly using an ultrasonic disperser to form a graphene dispersion;

[0037] The metal organic framework material and nano-alumina were respectively added to a surface modifier of 3% of their own weight for surface treatment, and stirred at 25°C for 30 minutes, wherein the MOFs were surface modified by using a silane coupling agent (A-174); the alumina was surface modified by using a titanate coupling agent; the EPDM rubber was pre-crushed into fine particles;

[0038] (2) Mixing the raw materials: stir half of the vinyl chloride-acrylate copolymer and EPDM rubber in a high-speed mixer for 8 minutes to mix them evenly; stir the remaining vinyl chloride-acrylate copolymer, polyetheretherketone, nano-titanium dioxide, metal organic framework material, nano-aluminum oxide and other additives (antioxidant, light stabilizer, plasticizer) in a high-speed mixer for another 7 minutes to mix them evenly;

[0039] While continuing to stir in the high-speed mixer, add the graphene dispersion through the side feed port, and add the grinding aid zinc stearate;

[0040] (3) Melt blending: The uniformly mixed materials were fed into a twin-screw extruder with the feed zone temperature at 200°C, the melting zone temperature at 335°C, and the mixing zone temperature at 300°C for melt blending, and the screw speed was adjusted to 30 r / min;

[0041] The melt-blended material is extruded through the die head of an extruder, rapidly cooled (air-cooled), pelletized, and dried to obtain high-temperature resistant and tough cable material pellets.

[0042] Embodiment 2: A high temperature resistant and tough cable material, made of the following components in parts by weight:

[0043] 40 parts of vinyl chloride-acrylate copolymer (viscosity average molecular weight 40,000 Da), 20 parts of polyether ether ketone (PEEK) (viscosity average molecular weight 35,000 Da), 12 parts of ethylene propylene diene rubber (EPDM), 1.5 parts of graphene, 3.5 parts of nano titanium dioxide (TiO2), 2.5 parts of metal organic framework material (UiO-66), 3.5 parts of nano alumina (Al2O3), 2 parts of antioxidant (2 parts of antioxidant 1010), 1 part of light stabilizer (Tinuvin 770), 3 parts of plasticizer (epoxidized soybean oil ESO), and 0.5 parts of grinding aid zinc stearate.

[0044] A method for preparing a high temperature resistant and tough cable material, such as Figure 1 As shown, the following steps are included:

[0045] (1) Raw material pretreatment: weigh each component raw material according to weight, and vacuum dry it at 100° C. for 4 h; add graphene to 22.5 parts by weight of isopropanol solvent, and disperse it evenly using an ultrasonic disperser to form a graphene dispersion;

[0046] The metal organic framework material and nano-alumina were respectively added to a surface modifier of 3% of their own weight for surface treatment, and stirred at 25°C for 30 minutes, wherein the MOFs were surface modified by using a silane coupling agent (A-174); the alumina was surface modified by using a titanate coupling agent; the EPDM rubber was pre-crushed into fine particles;

[0047] (2) Mixing the raw materials: stir half of the vinyl chloride-acrylate copolymer and EPDM rubber in a high-speed mixer for 5 minutes to mix them evenly; stir the remaining vinyl chloride-acrylate copolymer, polyetheretherketone, nano-titanium dioxide, metal organic framework material, nano-aluminum oxide and other additives (antioxidant, light stabilizer, plasticizer) in a high-speed mixer for another 10 minutes to mix them evenly;

[0048] While continuing to stir in the high-speed mixer, add the graphene dispersion through the side feed port, and add the grinding aid zinc stearate;

[0049] (3) Melt blending: The uniformly mixed materials were fed into a twin-screw extruder with a feed zone temperature of 180°C, a melt zone temperature of 320°C, and a mixing zone temperature of 300°C for melt blending, and the screw speed was adjusted to 25 r / min;

[0050] The melt-blended material is extruded through the die head of an extruder, rapidly cooled (in a cold water bath), pelletized, and dried to obtain high-temperature resistant and tough cable material pellets;

[0051] (4) UV curing: Spray a solution containing a photoinitiator on the surface of the extruded pellets; irradiate the material with UV light to initiate a cross-linking reaction between polymer chains. The curing time is 7 minutes.

[0052] Embodiment 3: A high temperature resistant and tough cable material, made of the following components in parts by weight:

[0053] 50 parts of vinyl chloride-acrylate copolymer (viscosity average molecular weight 50,000 Da), 10 parts of polyether ether ketone (PEEK) (viscosity average molecular weight 25,000 Da), 8 parts of ethylene propylene diene rubber (EPDM), 0.5 parts of graphene, 2 parts of nano titanium dioxide (TiO2), 1 part of metal organic framework material (MIL-101), 2 parts of nano alumina (Al2O3), 2 parts of antioxidant (2 parts of antioxidant 168), 1 part of light stabilizer (Chimassorb 944), 2 parts of plasticizer (dioctyl phthalate DOP), and 0.5 parts of grinding aid zinc stearate.

[0054] A method for preparing a high temperature resistant and tough cable material, such as Figure 1 As shown, the following steps are included:

[0055] (1) Raw material pretreatment: weigh each component raw material according to weight, and vacuum dry it at 120° C. for 2 h; add graphene to 7.5 parts by weight of isopropanol solvent, and disperse it evenly using an ultrasonic disperser to form a graphene dispersion;

[0056] The metal organic framework material and nano-alumina were respectively added to a surface modifier of 3% of their own weight for surface treatment, and stirred at 25°C for 30 minutes, wherein the MOFs were surface modified by using a silane coupling agent (A-174); the alumina was surface modified by using a titanate coupling agent; the EPDM rubber was pre-crushed into fine particles;

[0057] (2) Mixing the raw materials: stir half of the vinyl chloride-acrylate copolymer and EPDM rubber in a high-speed mixer for 10 minutes to mix them evenly; stir the remaining vinyl chloride-acrylate copolymer, polyetheretherketone, nano-titanium dioxide, metal organic framework material, nano-aluminum oxide and other additives (antioxidant, light stabilizer, plasticizer) in a high-speed mixer for another 5 minutes to mix them evenly;

[0058] While continuing to stir in the high-speed mixer, add the graphene dispersion through the side feed port, and add the grinding aid zinc stearate;

[0059] (3) Melt blending: The uniformly mixed materials were fed into a twin-screw extruder with a feed zone temperature of 220°C, a melt zone temperature of 320°C, and a mixing zone temperature of 300°C for melt blending, and the screw speed was adjusted to 35 r / min;

[0060] The melt-blended material is extruded through the die head of an extruder, rapidly cooled (air-cooled), pelletized, and dried to obtain high-temperature resistant and tough cable material pellets;

[0061] (4) UV curing: spray a solution containing a photoinitiator on the surface of the extruded pellets; irradiate the material with UV light to initiate a cross-linking reaction between polymer chains, and the curing time is 10 min;

[0062] (5) Microwave post-treatment: The UV-cured material is placed in a microwave device for microwave treatment to promote the cross-linking reaction inside the material; the microwave treatment time is 7 minutes and the power is 400W.

[0063] Comparative Example: A traditional PVC cable material formula, made from the following components in parts by weight:

[0064] 100 parts of polyvinyl chloride (PVC) resin, 50 parts of plasticizer (dioctyl phthalate DOP), 6 parts of stabilizer (calcium zinc composite stabilizer), 25 parts of filler (calcium carbonate), 1.5 parts of lubricant (calcium stearate), and 1 part of antioxidant (antioxidant 1010).

[0065] The preparation method of PVC cable material comprises the following steps:

[0066] (1) Raw material pretreatment: All solid raw materials are vacuum dried to remove moisture and dried at 100-120°C for 2-4 hours;

[0067] (2) Raw material mixing: polyvinyl chloride (PVC) resin, plasticizer, stabilizer, filler, lubricant, and antioxidant are mixed uniformly in a high-speed mixer;

[0068] (3) Melt blending: The uniformly mixed materials were fed into a twin-screw extruder with the feed zone temperature at 170°C, the melting zone temperature at 190°C, and the mixing zone temperature at 180°C for melt blending. The screw speed was adjusted to 25 r / min.

[0069] (4) Cooling and pelletizing: The melt-blended material is extruded through the die head of an extruder, rapidly cooled (in a cold water bath), pelletized, and dried to obtain conventional PVC cable material pellets.

[0070] Performance test: The cable materials prepared in Examples 1 to 3 and the comparative example were tested for high temperature resistance, mechanical properties, chemical corrosion resistance, electrical properties, and aging resistance;

[0071] 1. High temperature resistance test

[0072] 1.1 Heat Deformation Temperature (HDT)

[0073] According to ASTM D648 standard, the material was made into a specimen with a size of 127mmx12.7mmx6.4mm; a heat deformation temperature tester was used; the load was set to 1.80MPa (72.2kgf / cm 2 ), heating at a rate of 120°C / h; when the deformation of the sample under load reaches 0.34 mm, the temperature at this time is recorded as the heat deformation temperature (HDT).

[0074] As can be seen from Table 1, the dimensional stability of the high temperature resistant tough cable material of the present invention under high temperature conditions is significantly better than that of the traditional PVC cable material, especially Example 2 shows the best high temperature resistance and has the highest heat deformation temperature, and is suitable for occasions requiring higher heat resistance.

[0075] Table 1 Cable material heat deformation temperature (HDT) test results

[0076] Test items Heat Deflection Temperature (HDT) Example 1 120℃ Example 2 125℃ Example 3 115℃ Comparative Example 95℃

[0077] 2. Mechanical properties test

[0078] 2.1 Tensile strength

[0079] According to ASTM D638 standard, specimens with a length of 127 mm, a width of 12.7 mm, and a thickness of 4.0 mm ± 0.2 mm were made, with 5 specimens in each group; a universal material testing machine was used to fix the specimens in the fixture of the testing machine; the test speed was set to 50 mm / min; the test was started, and the maximum tensile force when the specimen broke was recorded; the tensile strength was calculated and the average value was taken.

[0080] As can be seen from Table 2, the high temperature resistant tough cable material of the present invention shows significant advantages in tensile strength; Example 2 has the highest tensile strength; and the comparative example (traditional PVC cable material) has the lowest tensile strength.

[0081] Table 2 Tensile strength test results

[0082]

[0083]

[0084] 3. Chemical corrosion resistance test

[0085] 3.1 Acid and alkali resistance test

[0086] The material was made into a sample with a size of 127mm×12.7mm×4.0mm (length×width×thickness), and soaked in 1M sulfuric acid at room temperature (23℃±2℃) for 48h; after soaking, the sample was taken out and cleaned with deionized water; the appearance changes of the sample such as color, gloss, surface roughness, etc. were observed; the tensile strength performance test was carried out and the data was recorded;

[0087] As can be seen from Table 3, the corrosion resistance of the high temperature resistant tough cable material of the present invention in an acid-base environment is significantly better than that of the traditional PVC cable material; among them, the tensile strength of Example 2 after acid and alkali immersion changes the least, showing the best corrosion resistance; the tensile strength of the comparative example decreases the most, indicating that the corrosion resistance of the traditional PVC cable material in an acid-base environment is poor.

[0088] Table 3 Acid and alkali resistance test results

[0089]

[0090] 4. Electrical performance test

[0091] 4.1 Dielectric properties test

[0092] According to ASTM D150 standard, the material is made into a circular specimen with a diameter of 25.4mm and a thickness of 1.5mm; a high-frequency dielectric tester is used, the specimen is placed between the electrodes of the tester, the test frequency is set to 1MHz, the room temperature is 23℃±2℃, the humidity is 50%±5%, and the dielectric constant and dielectric loss at this frequency are recorded; the data are calculated and recorded.

[0093] As can be seen from Table 4, the dielectric properties test results show that the high temperature resistant tough cable material of the present invention exhibits good characteristics in dielectric properties; Example 2 performs best in dielectric loss and has the lowest dielectric loss; the dielectric loss of the comparative example is the highest, indicating that the traditional PVC cable material is relatively poor in dielectric properties.

[0094] Table 4 Dielectric properties test results

[0095] Test items Dielectric constant (ε) Dielectric loss (tanδ) Example 1 3.2 0.02 Example 2 3.1 0.03 Example 3 3.3 0.015 Comparative Example 3.5 0.04

[0096] 5. Aging resistance test

[0097] 5.1 Thermal aging test

[0098] According to ASTM G164 standard, the material was made into specimens with a size of 127mmx12.7mmx6.4mm; a high-temperature aging box was used, the aging temperature was set to 90°C, and the aging time was 4 weeks; before the aging test began, the tensile strength performance test of the specimen was performed, and the initial value was recorded. After the aging test, the specimen was taken out for tensile strength performance test, the test results were recorded, and the percentage change relative to the initial value was calculated to evaluate the aging performance.

[0099] As can be seen from the results in Table 5, compared with the comparative example, the high temperature resistant tough cable material of the present invention has a smaller change in tensile strength after the high temperature aging test, showing better mechanical stability.

[0100] Table 5 Thermal aging test results

[0101]

[0102]

[0103] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A high temperature resistant and tough cable material, characterized in that: The invention is prepared from the following components in parts by weight: 40-50 parts of vinyl chloride-acrylate copolymer, 10-20 parts of polyetheretherketone, 8-12 parts of ethylene propylene diene rubber, 0.5-2 parts of graphene, 2-4 parts of nano titanium dioxide, 1-3 parts of metal organic framework material, 2-4 parts of nano aluminum oxide, 1-2 parts of antioxidant, 1-2 parts of light stabilizer and 2-4 parts of plasticizer.

2. A high temperature resistant and tough cable material according to claim 1, characterized in that: The viscosity average molecular weight of the vinyl chloride-acrylate copolymer is 20000-50000Da.

3. A high temperature resistant and tough cable material according to claim 1, characterized in that: The viscosity average molecular weight of the polyetheretherketone is 20000-40000Da.

4. A high temperature resistant and tough cable material according to claim 1, characterized in that: The antioxidant includes antioxidant 1010 and / or antioxidant 168, the light stabilizer is a hindered amine light stabilizer, and the plasticizer includes dioctyl phthalate and / or epoxidized soybean oil.

5. A method for preparing a high temperature resistant and tough cable material, characterized in that: The following steps are involved: (1) Raw material pretreatment: weigh each component raw material according to the weight ratio, and vacuum dry it at 100-120° C. for 2-4 hours; add graphene to an isopropanol solvent with a concentration of 15 times the weight of graphene, and disperse it evenly using an ultrasonic disperser to form a graphene dispersion; The metal organic framework material and nano-alumina are respectively added with a surface modifier of 3% of their own weight for surface treatment, and stirred at 25°C for 30 minutes; the EPDM rubber is pre-crushed into fine particles; (2) Mixing the raw materials: stir half of the vinyl chloride-acrylate copolymer and EPDM rubber in a high-speed mixer for 5-10 minutes to mix them evenly; stir the remaining vinyl chloride-acrylate copolymer, polyetheretherketone, nano-titanium dioxide, metal organic framework material, nano-aluminum oxide, antioxidant, light stabilizer, and plasticizer in a high-speed mixer for another 5-10 minutes to mix them evenly; While continuing to stir in the high-speed mixer, add the graphene dispersion through the side feed port; (3) Melt blending: The uniformly mixed materials are fed into a twin-screw extruder, the feed zone temperature is 180-220°C, the melting zone temperature is 320-350°C, the mixing zone temperature is 300°C, and melt blending is performed, and the screw speed is adjusted to 25-35 r / min; The melt-blended material is extruded through a die head of an extruder, rapidly cooled, pelletized, and dried to obtain high-temperature resistant and tough cable material pellets.

6. The method for preparing a high temperature resistant and tough cable material according to claim 5, characterized in that: While adding the graphene dispersion, 0.5 parts by weight of a grinding aid zinc stearate was added.

7. The method for preparing a high temperature resistant and tough cable material according to claim 5, characterized in that: The rapid cooling includes air cooling or cold water bath cooling.

8. The method for preparing a high temperature resistant and tough cable material according to claim 5, characterized in that: The method also includes (4) ultraviolet light curing: spraying a solution containing a photoinitiator on the surface of the extruded material; irradiating the material with ultraviolet light to initiate a cross-linking reaction between polymer chains, and the curing time is 5-10 minutes.

9. The method for preparing a high temperature resistant and tough cable material according to claim 5, characterized in that: The method also includes (5) microwave post-treatment: placing the UV-cured material in a microwave device and subjecting it to microwave treatment to promote the cross-linking reaction inside the material; the microwave treatment time is 5-10 minutes and the power is 300-500W.

10. The method for preparing a high temperature resistant and tough cable material according to claim 5, characterized in that: In the process of surface modification of metal organic framework materials and nano-alumina, silane coupling agents are used to modify the surface of MOFs; The surface of alumina was modified using titanate coupling agent.

Citation Information

Patent Citations

  • A high-temperature resistant and flame-retardant PVC cable material and its preparation method

    CN110218402B

  • Cable material with impact performance enhanced by methyl methacrylate copolymer

    CN106243688A

  • Cold-resistant and stretching-resistant cable material for high-voltage power transmission and preparation method thereof

    CN109679251A

  • Environmentally friendly and cold-resistant polyvinyl chloride elastomer composition and preparation method thereof

    WO2016192292A1

  • Flexible cable material having high tear resistance, low-temperature resistance and wear resistance, and cable

    WO2024212671A1